Plano de segurança em sistemas de abastecimento de água: limitações e tendências no meio urbano - Ventura, Katia Sakihama; Sardinha, Aline Souza; Rezende, Danilo (International Workshop for Innovation in Safe Drinking Water, 2022)
The newest model of the Water Security Plan (WSP) has been piloted in some countries to warn sanitation service managers about the risks to climate resilience (CR). The bibliometric analysis was performed (2015 to 2022) on the Web of Science database with the string "water safety, climate, risk, drinking water", operator AND in "all fields", merging complete records and quoting references from Vosviewer software. The results identified 65 international articles on WSP-CR, and six of them were selected in this analysis. Most of the available studies do not address threats from climate change in sanitation systems and river basins. The challenges of the WSP-CR applications are: i) data reliability, ii) the feasibility of implementing the model and the existence of few studies on this topic, and, iii) the complexity of the model in water supply systems, especially in small communities. Among the opportunities, the following stand out: the implementation of the plan with a sustainability and urban resilience bias leads to a better performance of the long-term water supply system to the public manager due to multidisciplinary aspects of decision makers.